Does central environmental inspection promote the industrial structure upgrading in China? An attention-based view - Wang, Biying; Ma, Chunhao; Wu, Jianzu (Frontiers in Environmental Science, 2022)
While central environmental inspection (CEI), a sort of campaign-style enforcement, has been adopted in China to tackle environmental issues, it is unclear if the CEI has promoted industrial structure upgrading. Based on a sample of 279 cities from 2011 to 2018 in China, this study investigates the impact of CEI on industrial structure upgrading and its intrinsic mechanism using the difference-in-differences approach (DID). The results reveal that (1) CEI significantly promoted industrial structure upgrading. (2) Local government environmental attention played a mediating role between CEI and industrial structure upgrading. (3) Further analysis revealed that the effect of CEI on industrial structure upgrading differed significantly with regional discrepancies and the officials’ promotion motivation. Specifically, the CEI had greater effects on the eastern region and those cities whose officials have a strong promotion motivation. This study contributes to industrial structure upgrading theoretical research and offers useful insights into the environmental governance of emerging countries.